The Hidden Cost of Specialization - Fabio Landini; Antonio Nicolò; Marco Piovesan (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2013)
Given the advantages of specialization, employers encourage their employees to acquire distinct expertise to better satisfy clients' needs. However, when the client is unaware of the employees' expertise and cannot be sorted out to the most competent employee by means of a gatekeeper, a mismatch can occur. In this paper we attempt to identify the optimal condition so an employer can eliminate this mismatch and offer a team bonus that provides the first-contacted employee with an incentive to refer the client to the correct expert. We show that the profitability of this referral contract increases with the agents' degree of specialization and decreases with the clients' competence at identifying the correct expert. Interestingly, a referral contract may be more profitable than an individual contract -that does not pay a team bonus- even if the former provides less incentive to the agents to improve their expertise. Thus, we provide a new rationale for the use of team bonuses even when the production function depends on a single employee's effort.
Keywords: C72; D01; D21; D86; M52; 330; Team and Individual Contracts; Matching Client-Expert; Incentives to Refer